The Potential Test of Vascular Arbuskula Mychorryza (VAM) Type on The Growth of Corn Plant ( Zea mays L.) on Inceptisol - Astri Hartaty Simanungkalit; Asmarlaili Sahar Hanafiah; Tengku Sabrina (Jurnal Agroekoteknologi, 2019)
Vascular Arbuskula Mycorrhiza (VAM) is a fungus that symbiosis with plant roots. Mycorrhiza can be found in almost 80% of plant species. This research aimed to examine the potential of Vascular Arbuskula Mycorrhiza isolated from several plant rhizosphere on the growth of corn plant (Zea mays L.) and nutrient uptake.Mycorrhizal isolates was collected from roots of wild ginger, bangle, turmeric and oil palm crop planted on Spodosol. Experimental design used Randomized Block Design with 8 treatments, that were the various of mycorrhizal isolates and 3 replications.This research was conducted at green house and laboratory. Potency of mycorrhizal isolates was tested on corn plants on Inceptisol. The results showed that the application of mycorrhizal isolates from oil palm’s roots planted on Spodosol increased corn’s growth (plant height, stem diameter, number of leaves and root dry weight) higher than growth on control and on other mycorrhizal treatments. The best treatment increased the NPK nutrient uptake was mycorrhizal isolates from oil palm’s roots planted on Spodosol.  Keywords : corn,inceptisol,mycorrhiza inoculums,oil palm,spices Potency of mycorrhizal isolates was tested on corn plants on Inceptisol. The results showed that the application of mycorrhizal isolates from oil palm’s roots planted on Spodosol increased corn’s growth (plant height, stem diameter, number of leaves and root dry weight) higher than growth on control and on other mycorrhizal treatments. The best treatment increased the NPK nutrient uptake was mycorrhizal isolates from oil palm’s roots planted on Spodosol.